Antibacterial Strategies: Multivalent Nanosheet Antibody Mimics for Selective Microbial Recognition and Inactivation (Adv. Mater. 22/2021). Issue 22 (1st June 2021) - Kang, Tae Woog; Hwang, In‐Jun; Lee, Sin; Jeon, Su‐Ji; Choi, Chanhee; Han, Juhee; So, Yoonhee; Son, Wooic; Kim, Hyunsung; Yang, Chul‐Su; Park, Jae‐Hyoung; Lee, Hwankyu; et al.
Abstract : In article number 2101376, Hwankyu Lee, Jong‐Ho Kim, and co‐workers report luminescent nanosheet artificial antibodies designed by assembling the multivalent recognition phases of tripeptides on transition metal dichalcogenide nanosheets for the selective recognition, rapid detection and identification, and eradication of pathogenic bacteria. The on‐demand luminescent artificial antibodies are employed for diagnosis and therapy of diseases induced by pathogenic bacteria.